Application of Simple Fish Processing Technology to Increase the Economic Income of the Oransbari Pantai Community: Penerapan Teknologi Sederhana Pengolahan Ikan untuk Meningkatkan Pendapatan Ekonomi Masyarakat Oransbari Pantai - Syahira, Syahira; Sigit Prafiadi; Wiska Baharuddin Cahdeso; Revolson Alexius Mege; Mario Parinsi Tulenan; Mercy Rampengan (Universitas Lancang Kuning, 2025)
A community empowerment activity has been carried out aimed at applying simple fish processing technology to improve the economy of the people of Oransbari Beach, South Manokwari, starting from the problem, namely that although there is abundant fisheries potential, it has not significantly increased the economic income of fishing communities because the selling value is not commensurate with production costs due to lack of there are efforts to handle post-catch and a lack of efforts to diversify post-harvest fishery products. The method applied is Andragogik (adult learning) with activity stages namely socialization, training, application of technology, mentoring and evaluation monitoring. The results achieved are (1) facilitated efforts to increase mastery of knowledge and skills in processing various processed fish and various flavors, (2) facilitated the design of one unit of fish dryer/grilling equipment for post-harvest fish processing, (3) facilitated the provision of a cooler (freezer) to prevent post-catch damage and storage of fish, (4) facilitated the procurement of packaging machines for various processed fish products, (5) facilitated increasing the capacity of Partner resources in mastering knowledge and simple marketing skills